تأثر تطبيق النموذج التعليمي لترقية إتقان مفردات اللغة العربية - Baihaqi, Muhammad; Muflihah; Irmawati; Syafa’ah, Ajeng Alyatus; Kholidiyah, Ananda Wifaq (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Issues in research it is how to teach vocabulary and how to apply the learning model (Mumtaz Review Course) the vocabulary of the Arabic language, and how did the application of the educational model affect the upgrade mastering Arabic vocabulary. Intructional model is method in which the teacher uses the student to deliver. The student is told to master vocabulary if he can students are required to translate vocabulary in different forms and to they pronounce and write the words again with the correct and to be a useful magazine of vocabulary, verbal or written.